Comprehensive research and risk assessment on the pollution profile of organic micropollutants (OMPs) in different types of citrus essential oils produced from waste citrus peels in Türkiye - Yuce, Beyza; Guzel, Baris; Canli, Oltan; Olgun, Elmas Oktem; Kaya, Derya; Asci, Burge; Hocaoglu, Selda Murat (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
This study was to investigate the presence of organic micropollutants (OMPs) and possible sources of PAHs in four different citrus peel oils (orange, mandarin, lemon and grapefruit) and a risk assessment was conducted. The concentrations of EPAH were found from 26.69 to 62 ng/g oil. Naphthalene, acenaphthene, acenaphthylene, phenanthrene and fluoranthene are the dominant PAHs. The source of the PAH compounds in the samples was predominantly of pyrogenic origin. EPCB results range between 0.726 and 3.596 mu g/kg oil, with PCB 153 and PCB 138 being the most detected in the samples. EOCP results were found in the range of 0.450-2.171 mu g/kg oil. p,p'-DDD, p,p '-DDE, p,p '-DDT and alpha-HCH among the samples was detected at a significant rate. In the citrus oils, EPCDD/F values were found to be 0.0073-0.3076 WHO-TEQ pg/g oil, while EDL-PCB values varied between 0.00259 and 0.00829 WHO-TEQ pg/g oil. None of these results exceed the limits of the European Commission and Turkish Food Codex Regulations. While PCB 77 and PCB 81 were more abundant in DL-PCBs than other congeners, this situation was 2378-TCDD and 12378-PeCDD in PCDD/Fs. In human risk assessment, HQ, HI, and TLCR values of some OMPs indicate that there is no risk of carcinogenic or non-carcinogenic hazards for both children and adults.
Keywords: Citrus essential oils; Organic micropollutants (OMPs); Risk assessment; Source identification; POLYCYCLIC AROMATIC-HYDROCARBONS; CHROMATOGRAPHY-MASS SPECTROMETRY; URBAN SOILS; CHEMICAL-COMPOSITION; SURFACE SEDIMENTS; WETLAND SOILS; PAHS; PESTICIDES; FRUITS; Chemistry; Food Science & Technology